2021
DOI: 10.1016/j.brs.2021.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical mechanisms of electroconvulsive therapy-induced volume expansion in the medial temporal lobe: A longitudinal in vivo human imaging study

Abstract: Background: Electroconvulsive therapy (ECT) applies electric currents to the brain to induce seizures for therapeutic purposes. ECT increases gray matter (GM) volume, predominantly in the medial temporal lobe (MTL). The contribution of induced seizures to this volume change remains unclear. Methods: T1-weighted structural MRI was acquired from thirty patients with late-life depression (mean age 72.5 ± 7.9 years, 19 female), before and one week after one course of right unilateral ECT. Whole brain voxel-/deform… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…First, seizure is an important therapeutic component of ECT [ 56 ], but the impact of seizure on neuroplasticity and clinical outcomes was not assessed with this investigation. Seizure activity may be related to neuroplasticity with and without E-field generation (i.e., Metrazol therapy) [ 57 , 58 ]. The lateralization of ictal power with RUL electrode placement suggests that E-field and ictal power may be interrelated [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, seizure is an important therapeutic component of ECT [ 56 ], but the impact of seizure on neuroplasticity and clinical outcomes was not assessed with this investigation. Seizure activity may be related to neuroplasticity with and without E-field generation (i.e., Metrazol therapy) [ 57 , 58 ]. The lateralization of ictal power with RUL electrode placement suggests that E-field and ictal power may be interrelated [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent work by Takamiya et al, E-field models were computed in thirty depressed subjects receiving RUL ECT, a subgroup of which incorporated DTI-derived anisotropic conductivity in the models. The E-field correlations with regional brain volumetric changes were similar between both models [ 57 ]. Future work will need to validate E-field modeling accuracy (with or without DTI) prior to clinical use (“E-field-informed ECT”).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to a recent anatomical parcellation study from GEMRIC [14], the structural increase in patients receiving ECT was widely distributed across the brain. The fact that the highest statistical peak was found in the right hippocampal area could be attributed to the electrode placement and coinciding electric field strength [31-32], presumably due to the majority of the patient sample used in this study receiving RUL stimulation. Again, in line with the previous report from GEMRIC, the large-scale volume increase was not related to clinical response, as indicated by both the factorial ANOVA and multiple regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with these preclinical ndings, recent large-scale studies in the Global ECT-MRI Research Collaboration (GEMRIC) dataset 15 found robust volume increases 16,17 in a wide range of cortical and subcortical regions, which correlated with the number of ECT sessions. Subsequent EF modeling based on the individual head MRI consistently demonstrated that the ECT-induced EF strongly correlated with volume increase [18][19][20] . These results veri ed that despite the widespread activation of the brain through seizure, the direct electrical stimulation effect of ECT is much more spatially selective and individually diverse than rst assumed.…”
Section: Introductionmentioning
confidence: 99%